A Mirror of Saudi Social Reform: An Analysis of Haifa al-Mansour's Film "Wadjda" Tzvetan Todorov's Narrative Theory - Nabilah Ulil Fikriyah; Muassomah Muassomah (Mantiqu Tayr: Journal of Arabic Language, 2025)
The film Wadjda by Haifaa al-Mansour is a cinematic work that portrays the struggles of a young girl in Saudi Arabia as she navigates rigid social norms. In recent decades, Saudi Arabian society has undergone various social reforms aimed at redefining the role of women, including easing restrictions on education and social participation. This context is significant to analyze, as films often serve as a medium that reflects and critiques ongoing social dynamics. This study aims to explore how the film reflects the ongoing social reforms within Saudi society. Tzvetan Todorov's narrative theory outlines five stages: equilibrium, disruption, recognition, resolution, and new equilibrium. The method used is narrative analysis with a qualitative approach. Data were collected through observation of narrative elements in the film and analyzed based on Todorov's five stages. The analysis process includes identifying the initial equilibrium, the disruption faced by the main character, the recognition of the arising situation, efforts to remedy it, and the achievement of a new equilibrium. The results show that Wadjda begins with an equilibrium, where Wadjda lives a typical everyday life. Disruption occurs when Wadjda expresses a desire to buy a bicycle, which conflicts with gender norms in her society. Recognition of this challenge drives Wadjda to pursue her dream, ultimately leading to a positive shift in societal views on women. Through Todorov's narrative analysis, it becomes evident that the film effectively illustrates how small changes can spark discussions on women's rights and individual freedom within a conservative cultural context. This study contributes to the academic discourse on the intersection between narrative structures and social reform by providing a case study that applies Todorov's theory to Arabic cinema. It also highlights the significance of Wadjda as a cultural artifact that reflects evolving gender norms in Saudi Arabia, thereby enriching the understanding of how media serves as a lens for societal transformation. Despite its insights, this study is limited in scope as it focuses solely on Wadjda without comparative analysis with other films addressing similar themes. Additionally, the study does not consider audience reception, which could provide a deeper understanding of the film's societal impact. Future research could address these gaps by incorporating comparative studies or exploring the film's reception in both local and global contexts.